Comparative study on the international coal trade network before and after COVID-19 outbreak - Zhao, Jingying; Huang, Hui (Frontiers in Energy Research, 2023)
The COVID-19 that broke out at the end of 2019 led countries to implement strict blockade measures to curb the spread of the virus. These measures have seriously disrupted coal import and export trade, causing a significant impact on the coal trade network. This study aims to investigate the disparities between coal trade networks pre- and post-COVID-19 outbreak. Firstly, employing Complex Network Theory, we construct global coal trade networks for the years 2019 and 2020. Subsequently, utilizing a cascading failure model, we develop a coal supply risk propagation framework. Through an analysis of network topology and theoretical supply risk propagation, we explore the similarities and differences of the coal trade networks during these two years. Our findings reveal a decrease in trade tightness in the coal trade network of 2020 compared to 2019. Moreover, the Netherlands no longer retains its significance as an important trade hub country in 2020. Looking at the theoretical perspective of supply risk transmission, we observe that in 2020, COVID-19 resulted in a higher number of countries experiencing crisis outbreaks compared to 2019. However, it's noteworthy that the core countries within the coal trade network have remained consistent, and their roles as either net importers or net exporters have not changed. Interestingly, in 2020, the risk associated with coal supply does not conform to the spatial patterns typically seen in trade. For instance, the Russian Federation, identified as a country facing a crisis outbreak, transmits supply risks to geographically distant regions in West Asia, including countries like Ghana and Western Sahara.